Wind profiles in Peninsular Malaysia: a comprehensive upper air analysis - Alias, Mohd Shahidi; Mohd Rafie, Azmin Shakrine; Abdul Hamid, Mohd Faisal; Gires, Ezanee; Mohd Aris, Khairul Dahri (Penerbit Universiti Kebangsaan Malaysia, 2024)
Understanding the atmospheric properties and patterns is crucial in empowering Malaysia’s national aerospace blueprint, national space, and legislation. While various policies have been enacted and implemented, there is a lack of information on the wind profile, specifically the upper air across Peninsular Malaysia. Realising the need to establish a standard guideline for national reference, future research, space-aerospace application, and legislation, this study was performed to develop the first wind profile analysis of upper air in Peninsular Malaysia. Relevant data from the Malaysian Meteorology Department was collected for analysis and evaluation. Specifically, a meteorology balloon attached with a sounding radiosonde was used to record data at 0000UTC (0800 h LT) and 1200UTC (2000 h LT) on the 15th day of each month for 7 years (from 2015 to 2021) at the KLIA and Kuantan Meteorology Stations for the wind profiling analysis. The daily overall data collection was recorded accurately once the balloon’s rising rate stabilises from vertical air current (katabatic or anabatic winds). Subsequently, the collected data were evaluated in terms of the minimum, maximum, and average wind speeds for each year and time. Finally, the average wind speed of each year and time were combined to generate the Peninsular Malaysia wind profile. Based on the results, the projected wind profile for both stations identified three peaks of discrete sine wave flow type with low-speed wind profile in Peninsular Malaysia. The three peaks amplified the highest air velocity, whereby the 1st and 2nd peaks were located at the troposphere layer from 9,000 m to 12,000 m altitude (average wind speed of 10.8 ms-1) and 12,000 m to 18,000 m altitude (average wind speed of 13.7 ms-1). The 3rd peak was located at the stratosphere layer from 18,000 m to 32,000 m altitude (average wind speed of 15.2 ms-1). Since East Malaysia is located on the same equatorial line, the wind profile is hypothetically the same and exhibits only slight differences. In short, the established wind profile of upper air in Peninsular Malaysia in this study would facilitate other future studies and assist long-term planning of Malaysia’s airspace legislation.